Increasing Public Awareness of Information on Billboards about The Exemption of Land and Building Taxes Fines in Sidoarjo Regency - Bagus Kurniawan Susanto; Septian Dwi Pratama; Vonda Aprilianto (LONTAR: Jurnal Ilmu Komunikasi, 2025)
This study aims to measure the level of public awareness of Sidoarjo Regency towards information on PBB fine amnesty delivered through billboards, especially along Jalan Pahlawan. The research method used was a survey involving 100 respondents aged 25-45 years who had experience crossing Jalan Pahlawan. Data analysis used the Customer Response Index (CRI) with a focus on the awareness and comprehend stages.  The results of the study showed that the level of public awareness of information on PBB fine amnesty through billboards was quite high, with a percentage reaching 88%. This indicates that billboards are effective in conveying public information to the public. In addition, the CRI analysis also showed that most respondents were able to understand the information conveyed on the billboards regarding the PBB fine amnesty program.